ANALYSIS OF IMPLEMENTATION OF MERDEKA CURRICULUM IN PRIMARY SCHOOLS - Khoerunissa, Jihan; Palestin, Balqis Tsuroyya; Ramadiana, Najia; Riani, Rinrin; Zamalududin, Abdul Zabar Muhammad; Rohman, Opik Ali; Fitriyani, Yani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
The independent curriculum is currently being hotly discussed in the realm of knowledge. This situation is tied to the ideals expressed by President Joko Widodo aimed at giving birth to a golden Indonesia in 2045. conveyed by President Joko Widodo. Steps that can be taken to give birth to these ideals are the implementation of an independent curriculum in each school. The aim of this research is to provide an explanation of the conceptual study regarding the independent learning curriculum that has been implemented in each elementary school for the 2022/2023 academic year. The library research method is the method used in this research in descriptive qualitative form. The data collection method used is document study, which involves collecting journals, books and other related sources. then tested and tested. After going through the data collection process, it is then continued with testing and comparing the data obtained and then presenting it in the form of a scientific article. The technical analysis used is descriptive/content analysis. Based on the analysis carried out, the final result was that the independent curriculum moves students to form independent, creative and innovative individuals. Seeing that the global environment is increasingly sophisticated and competition is getting stronger, students need to have this ability to be better prepared to experience future challenges and prepare Indonesia for greater success. To prevent errors and maintain the accuracy of the analysis data, a literature check is carried out by re-reading the literature and paying close attention to the supervisor's review.